Fiscal Policy and Economic Performance of Pakistan: Trends and Analysis - Naverah Mahtab; Saima Shafique; Shah, Syed Arshad Ali (Journal of Business & Tourism, 2023)
This research is to find the impact of fiscal policy in economic growth of Pakistan. To fulfill this purpose the time series data from 1991-2021 is used. The data source is Economy Survey of Pakistan and WDI. In this analysis with respect to first Augmented Dicky Fuller unit root test is implementing for checking the stationarity of the variables. At order 1, the all variables are integrated. Secondly, the Least Square (Gauss Newton/ Marquardt Steps) is employed to recognize the Pakistan’s fiscal policy has affected the country’s economic condition. This finding suggests that the gross fixed capital formation, labour force participation rate, total government revenue is positively associated to the growth rate and total expenditure is negatively relate to the economic growth. This research result shows the significant the Pakistan’s fiscal policy has affected the country’s economic condition.